Effect of different weed control periods on nutrients uptake by field pea and weeds - Singh, Mainpal; Kumar, Rajesh (Annals of Agricultural Research, 2016)
The field experiment was conducted during at 2008-09 and 2009-10 at Pulse Research Area of Chaudhary Charan Singh University Hisar to find out the effect of critical period of weed competition on nutrient uptake by weeds and field pea. Maximum NPK uptake by weed was recorded under the weedy check treatment followed by the weedy up to the 100 days after sowing (DAS) treatments. Weed free up to harvest of crop recorded statistically similar nutrients uptake by grain and stover of crop with weed free up to 80, 100 DAS and weedy upto 20 DAS treatments.